Effects of self-controlled practice and focus of attention on free throw accuracy: Exploring optimal theory among skilled basketball players - Shooli, M.; Saemi, E.; Boushehri, N. S.; Seifourian, M.; Simpson, T. (Human Movement Science, 2024)
Based on the OPTIMAL theory of motor learning (Wulf & Lewthwaite, 2016), optimal motor performance and learning will occur through the influence of the two motivational factors of enhanced expectancies and autonomy support (self-controlled practice) as well as the attentional factor of the external focus of attention. Recently, some researchers tested this theory on different motor tasks using novices. However, it seems that this theory has not been tested in skilled athletes. Therefore, the aim of the present study was to investigate the effect of self-controlled practice and focus of attention on the accuracy of free throws of skilled basketball players. The participants were 56 skilled adult basketball players (28 men; average age = 27.75 ± 3.31 years; 28 women, average age = 27.18 ± 3.63 years) who were randomly divided into two self-control and yoked groups. Each group performed 80 basketball free throw trials in four different attention conditions (external, internal, holistic, control) as a counterbalance, so that each participant made 20 basketball free throws in each attention condition. The results showed that skilled basketball players in the self-controlled group performed better than the yoked group when they could choose the color of the ball. The results also showed that focusing on external or holistic cues compared to focusing on internal cues improved basketball free throw performance in skilled players. However, the results did not show a difference between external and holistic attention with the control condition. The control condition was also similar to the internal attention condition. In summary, the results of this research could only partially support the OPTIMAL theory and showed that each of the two variables of self-controlled practice and external or holistic focus of attention separately and independently affect the motor performance of skilled basketball players and their additive effect was not observed. It is suggested that coaches try to use autonomy support as well as external or holistic focus of attention in practical situations to improve the motor performance of skilled athletes.